2011
DOI: 10.1093/carcin/bgr045
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate-mediated chemoprevention of experimental hepatocarcinogenesis involves Nrf2-regulated antioxidant mechanisms

Abstract: Hepatocellular carcinoma (HCC), one of the most prevalent and lethal cancers, has shown an alarming rise in the USA. Without effective therapy for HCC, novel chemopreventive strategies may effectively circumvent the current morbidity and mortality. Oxidative stress predisposes to hepatocarcinogenesis and is the major driving force of HCC. Pomegranate, an ancient fruit, is gaining tremendous attention due to its powerful antioxidant properties. Here, we examined mechanism-based chemopreventive potential of a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 56 publications
16
85
0
Order By: Relevance
“…Pomegranate has been known to posses considerable pharmacological properties as pomegranate peel is a rich source of antioxidants, especially polyphenols. In some recent studies, pomegranate fruit and flower extracts exhibited free-radicals scavenging properties with simultaneous potent hepatoprotection against chemically induced liver damage in rodents 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate has been known to posses considerable pharmacological properties as pomegranate peel is a rich source of antioxidants, especially polyphenols. In some recent studies, pomegranate fruit and flower extracts exhibited free-radicals scavenging properties with simultaneous potent hepatoprotection against chemically induced liver damage in rodents 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…DENA is reported to be hepatotoxin and the hepatocarcinogenic agent [12]. In the present study, DENA induced hepatocellular damage is clearly evidenced by the marked elevation in serum SGPT, SGOT, GGTP, ALP and decrease level of glucose in the liver tissue, These biochemical marker enzymes are indicators of tumor response [13].…”
Section: Discussionmentioning
confidence: 54%
“…The best results were observed with the 50mg/kg/day dose. In this respect, Bishayee et al (2011) found that pomegranate may act through the induction of Nrf2-regulated cytoprotective enzymes, which results in enhancing the excretion of the electrophilic carcinogen and reducing the formation of free radicals inductors of tumorigenesis. In contrast, the 75 mg/kg dose of PGE did not affect the bioavailability of this xenobiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover certain reports have shown considerable antioxidant activities of Punica granatum in several in vitro and in vivo experimental models (Chidambara et al, 2002;Cerda et al, 2003;Ricci et al, 2006;Bishayee et al, 2011). Such effects have been attributed to its effective action against ROS (Ozgen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%